Potential Replication of Induced Pluripotent Stem Cells for Craniofacial Reconstruction - Fu, Yao; Deng, Shuwen; Wang, Jing; Chen, Zhaozhao; Zhang, Shu; Wu, Songtao; Jiang, Yan; Ye, Ling; Peng, Qiang; Lin, Yunfeng (Current Stem Cell Research & Therapy, 2014)
The craniofacial region contains many specified tissues, including bone, cartilage, muscle, blood vessels, fat, skin and neurons. A defect or dysfunction of the craniofacial tissue after post-cancer ablative surgery, trauma, congenital malformations and progressive deforming skeletal diseases has a huge influence on the patient’s life. Therefore, functional reconstruction of damaged tissues is highly sought. The use of cell-based therapies represents one of the most advanced methods for enhancing the regenerative response for craniofacial wound-healing. The recently acquired ability to reprogram human adult somatic cells to induced pluripotent stem cells (iPSCs) in culture may provide a powerful tool for in vitro disease modeling and an unlimited source for cell replacement therapy. This review focuses on the generation, biological characterization and discussion of the potential application of iPSCs for craniofacial tissue-engineering applications.
Keywords: somatic cells